PENGARUH PENILAIAN PRESTASI KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN KEPEGAWAIAN - Tony Nursofyan; Ahmad Alim Bachri; Rini Rahmawati (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
The research aims to determine and analyze the influence of performance appraisal and workmotivation towardthe job satisfaction of employees in the BKD of Tanah Laut District.The population of this research is 41 people by using Multiple Regression Analysis Method. It is performed to determine whether the independent variable (performance appraisal and work motivation) partially influence the dependent variable (job satisfaction).The results on the BKD of Tanah Laut District indicate the absence of significant influence partially between the independent variables of performance appraisal toward the dependent variable of job satisfaction as well as the independent variable of work motivation which shows positive and significant influence on the dependent variable of job satisfaction.